Lose, team, lose! - Stine, R. L.; Park, Trip (New York : HarperTrophy, 2008)
Bernie Bridges and his teammates need to find a way to get Jennifer off the all-boys football team before they are forced to play the National Champion Bone-Breakers.
"A Parachute Press Book.".
3.1
3-6
Keywords: Boarding schools -- Juvenile fiction; Football -- Juvenile fiction; Schools -- Juvenile fiction; Boarding schools -- Fiction; Football -- Fiction; Schools -- Fiction; Football -- Fiction; Private schools -- Fiction; School stories